Neuromuscular responses of elite skaters during different roller figure skating jumps - Dias Pantoja, P.; Mello, A.; Veiga Liedtke, G.; Kanitz, A. C.; Lusa Cadore, E.; Santana Pinto, S.; Lima Alberton, C.; Martins Kruel, L. F (Journal of Human Kinetics, 2014)
This study aimed to describe the neuromuscular activity of elite athletes who performed various roller figure skating jumps, to determine whether the muscle activation is greater during jumps with more rotations and in which phase the muscles are more active. This study also aimed to analyze if there is any difference in the muscle activity pattern between female and male skaters. Four elite skaters were evaluated, and each participated in two experimental sessions. During the first session, anthropometric data were collected, and the consent forms were signed. For the second session, neuromuscular data were collected during jumps, which were performed with skates at a rink. The following four roller figure skating jumps were evaluated: single Axel, double Axel, double Mapes and triple Mapes. The neuromuscular activity of the following seven muscles was obtained with an electromyograph which was fixed to the waist of each skater with a strap: biceps femoris, lateral gastrocnemius, tibialis anterior, rectus femoris, vastus lateralis, vastus medialis and gluteus maximus. The signal was transmitted wirelessly to a laptop. During the roller figure skating jumps, the lateral gastrocnemius, rectus femoris, vastus lateralis, biceps femoris and gluteus maximus, showed more activation during the jumps with more rotations, and the activation mainly occurred during the propulsion and flight phases. Female skaters demonstrated higher muscle activities in tibialis anterior, vastus lateralis, vastus medialis and gluteus maximus during the landing phase of the triple Mapes, when compared to their male counterparts. The results obtained in this study should be considered when planning training programs with specific exercises that closely resemble the roller figure skating jumps. This may be important for the success of elite skaters in competitions.